Memory of the Former Future: Yevgeny Yevtushenko Has Died. (2nd January 2019) - Shubinskii, Valerii
Abstract : When well-known poet Yevgeny Yevtushenko died in 2017, a number of obituaries appeared in Russia and abroad. This one argues that the poet is important not so much for his poetry, but for the record it gives of the feelings and ambitions of people in his time.